Strengthening Physical and Financial Capital for Financial Self-Reliance: An Empowerment Model for Fisher Groups A Case Study of PT WHW's CSR Program in Sungai Tengar Hamlet - Rina Ekawati; Ari Djanuar Prasetyo (Bulletin of Science Education, 2026)
Fisherfolk group empowerment programs have predominantly focused on providing fishing equipment, with limited integration of financial capacity strengthening as a prerequisite for achieving business self-reliance. Consequently, increased productivity has not always been accompanied by improved financial management and business sustainability among fishers. This study aims to analyze the impact of fisherfolk group empowerment through the provision of fishing gear and the development of group savings in fostering the financial independence of fishing enterprises. A qualitative case study approach was employed. Data were collected through in-depth interviews, participant observation, document analysis, and Focus Group Discussions (FGDs), and were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and verification. The findings indicate that the provision of fishing gear enhances production capacity by strengthening physical capital, while the development of group savings reinforces financial capital through the cultivation of saving behavior, the accumulation of collective funds, and improved self-financing capacity. The integration of these interventions reduces dependence on informal lending, strengthens business resilience against risks, and enhances the group's capacity to manage economic assets sustainably. The study concludes that the financial independence of fishing enterprises is determined not only by increased income but also by the synergy between strengthened physical and financial capital supported by effective group institutions. Furthermore, this study proposes a conceptual empowerment model integrating the Sustainable Livelihood Framework, Community Empowerment Theory, Financial Capability Theory, and Social Capital Theory as a foundation for developing more sustainable fisherfolk empowerment policies.